2009
DOI: 10.1017/s1816383110000056
|View full text |Cite
|
Sign up to set email alerts
|

What does ‘intent to destroy’ in genocide mean?

Abstract: Genocide is a crime with a double mental element, i.e. a general intent as to the underlying acts, and an ulterior intent with regard to the ultimate aim of the destruction of the group. The prevailing view in the case-law interprets the respective 'intent to destroy' requirement as a special or specific intent (dolus specialis) stressing its volitional or purpose-based tendency. While this view has been followed for a long time in legal doctrine without further ado, it has recently been challenged by knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…49 It is in that regard they define genocide as a crime with a double mental element, ie, a general intent as to the underlying acts, and an ulterior intent with regard to the ultimate aim of the destruction of the group. 50,51 Similarities and Differences Observed from the Narratives of Respondents Similarities and differences from the respondents in terms of the identity change were found. This corroborates the idea of the prior studies that indicated that people possess multiple constructions of self that differ in activation across situations.…”
Section: Moral Reconstructionmentioning
confidence: 80%
“…49 It is in that regard they define genocide as a crime with a double mental element, ie, a general intent as to the underlying acts, and an ulterior intent with regard to the ultimate aim of the destruction of the group. 50,51 Similarities and Differences Observed from the Narratives of Respondents Similarities and differences from the respondents in terms of the identity change were found. This corroborates the idea of the prior studies that indicated that people possess multiple constructions of self that differ in activation across situations.…”
Section: Moral Reconstructionmentioning
confidence: 80%
“…In the case of genocide, the general intent relates to the opening paragraph as well as to the acts listed in the offence and directed against one of the protected groups. (Ambos, 2009: 834).…”
Section: What Is Genocide?mentioning
confidence: 99%
“…Kai Ambos (2009: 833) has attempted to illustrate the two separate mental elements: the crime of genocide, by what he described as “general intent” or dolus, and an additional “intent to destroy” 3 as provided by the International Commission of Inquiry on Darfur. 4 A general intent normally relates to all objective elements of the offence definition (actus reus) and has now been defined in international criminal law by Article 30 of the Statute of the ICC as basically encompassing a volitional (intent) and/or a cognitive or intellectual (knowledge) element.…”
Section: What Is Genocide?mentioning
confidence: 99%
“…Kai Ambos, 55 as well as Ugur Üngör and Mehmet Polatel, 56 therefore distinguish three different levels of perpetrators: high level perpetrators, mid level perpetrators and low level perpetrators, also considered foot soldiers or in the case of the Armenian genocide civilians and gendarmes. The high level perpetrators create the ideological framework in which genocidal violence gets sanctified.…”
Section: From Ideology To Actionmentioning
confidence: 99%